Residual elastic strain evolution due to thermal cycling of a ceramic-metal composite (WC-Cu) via high energy X-ray diffraction and analytical modeling. (January 2023) - Ferguson, John I.; Beaudoin, Armand J.; Scofield, Gregory D.; Ko, J.Y. Peter; Nygren, Kelly E.; Wang, Yujie; Caccia, Mario; Sandhage, Kenneth H.; Sangid, Michael D.
Abstract: Residual stress, when superimposed with in-service loading, can significantly reduce the lifetime and performance of a component. Ceramic-metal composites are susceptible to residual stresses due to the thermal expansion mismatch of the ceramic and metallic phases. The WC-Cu composite explored in the present study provides a promising combination of thermal conductivity and strength properties, while exhibiting counterintuitive improvements in strength and ductility after thermal cycling. This work quantifies the evolution of the residual elastic strains as a result of processing and cyclic thermal loading in a co-continuous WC-Cu composite through experimental high energy X-ray diffraction and kinetics-based modeling. Both analyses indicate that processing-induced residual tensile stress in the copper phase is relieved upon subsequent thermal cycling, with kinetics modeling revealing the cyclic-dependent nature of the active power-law creep mechanisms. The results indicate that, through stress relaxation, this material system maintains structural stability during thermal cycling. The illustrated kinetics of relaxation can inform general material processors and designers of ceramic-metal composites to minimize detrimental residual stress and improve performance of these material systems. Graphical abstract: Unlabelled Image Highlights: WC-Cu composite exhibited higher strength and ductility after thermal cycling. Energy Dispersive X-ray Diffraction (EDD) was performed on a series of samples. EDD revealed reduced processing-induced residual tensile stress in Cu after cycling. Kinetics modeling concurred with EDD, identifying active power-law creep mechanism. Characterization demonstrated a near single crystal orientation of the Cu phase.